Seedling Community in a Patchy Tropical Vegetation Under the Influence of Bamboos - Rother, Debora C.; Gorgens, Eric; Guerin, Natalia; Rodrigues, Ricardo R.; Pizo, Marco A. [UNESP] (Sage Publications Inc, 2018)
As a group adapted to invade disturbed sites, bamboos can dominate extensive areas and, thus, alter vegetation structure and dynamics. However, the effect of bamboo expansion associated to human activity on seedling communities in tropical forests remains poorly known. We investigated the correlation of the native bamboo Guadua tagoara presence for a year on the abundance, richness, diversity, dominance, evenness, emergence, mortality, and growth of the first months of the native seedlings establishment in an Atlantic forest area, Sao Paulo State, Brazil. Bamboo presence favored the initial establishment of the palm Euterpe edulis seedlings but altered seedling community structure as a whole. Species richness did not differ between bamboo and nonbamboo dominated habitats, but abundance, diversity, and evenness did. Bamboo habitats showed higher seedling abundance, emergence, and mortality than in habitats without bamboos. However, diversity was lower in these habitats. Our results shed light on the role of bamboo presence in limiting early establishment of native seedlings but favoring the first months of establishment of E. edulis, the dominant species in bamboo habitats (70%). Therefore, the monitoring of more specific variables could be included (i.e., bamboo culm density, soil type, decomposition of organic matter, fauna living, or foraging in bamboos) in future studies to better understand the consequences of bamboo dominance on the recruitment and dynamics of tropical forests biodiversity in the long term.
Keywords: assembly rules; ecological filters; invasive native bamboos; seedling recruitment